Sintesa dan Karakterisasi Katalis CaO-MgO/KF untuk Konversi Trigliserida Menjadi Monogliserida dari Minyak Kelapa Sawit - Khairunisa, Amira Zalwa; Selastia Yuliati; Mustain (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study aims to synthesize and characterize CaO-MgO/KF catalyst derived from dolomite sourced from Gresik, East Jawa, for the conversion of triglycerides into monoglycerides via glycerolysis of palm oil. The dolomite was calcined at 800 ℃ to produce active CaO and MgO phases. The catalyst were impregnated with 2% and 3% potassium fluoride (KF) by weight, followed by recalcination at various temperatures of 400, 450, 500, 550, and 600 ℃ for 4 hours. Characterization included basic site quantification via acid-base titration and morphological and elemental analysis using SEM-EDS. The result showed that the catalyst with 3% KF and calcination at 550 ℃ exhibited the highest basic site density of 12,3 mmol/g, along with a rough, porous surface morphology conducive to catalytic activity. Glycerolisis testing demonstrated the highest monoglyceride yield of 56% under these optimum condition. The addition of KF enhanced the basic strength and efficiency of the catalyst. This study confirm that CaO-MgO/KF catalyst synthesized from dolomite are promising as efficient and environmentally friendly heterogenous catalyst for monoglyceride synthesis.